Case report: The case of T-cell acute lymphoblastic leukemia treated with chemotherapy followed by anti-CD7 CAR-T cells using retroviral vector - Zhou, Huanhuan; Zhu, Wenxiang; Ma, Qihong; Liu, Ning; Jin, Mengdi; Feng, Yaru; Zhao, Lijun; Sun, Rui; Li, Rongyou; Li, Huaxiu; Shi, Yuanyuan; Wang, Jianxun; et al. (Frontiers in Immunology, 2025)
CD7-targeted chimeric antigen receptor-T (CAR-T) cell therapy has shown great promise in the treatment of relapsed/refractory T-cell acute lymphoblastic leukemia (T-ALL). In this study, we reported a case of a 34-year-old male patient with T-ALL who finally developed multi-line drug resistance and refractoriness after multiple lines of high-intensity chemotherapy. After physician evaluation, this patient received allogeneic hematopoietic stem cell transplantation (allo-HSCT). Then, The patient remained in complete remission (CR) for four months before a relapse with 26.64% chimerism rate, so he was treated with allogeneic anti-CD7 CAR-T cells after chemotherapy reducing the tumor burden. The CAR-T product was a novel anti-CD7 CAR-T based on retroviral vectors (RV). After infusion, the patient achieved CR within 1 month after anti-CD7 CAR-T infusion and the remission has been ongoing for 9 months to date. Cytokine release syndrome (CRS) 1 was experienced while no immune effector cell-associated neurotoxicity syndrome (ICANS) was found. In addition, CAR copy number peaked at 350, 758 copies/μg on day 6. This case report of clinical treatment of T-ALL with anti-CD7 CAR-T cells prepared using a retroviral vector without gene editing and combined with chemotherapy, which demonstrated that the RV-based anti-CD7 CAR-T cells had good therapeutic effect and high safety in triple-refractory T-ALL patients.